Synthesis and Supramolecular Assembly of a Terrylene Diimide Derivative Decorated With Long Branched Alkyl Chains - Guo, Zongxia; Zhang, Xiao; Zhang, Lu; Wang, Yujiao; Feng, Weisheng; Sun, Kai; Yi, Yuanping; Li, Zhibo (Frontiers in Chemistry, 2019)
Terrylene diimide derivatives are pigments for dyes and optoelectric devices. A terrylene diimide derivative N,N'-Di(1-undecyldodecyl)terrylene-3,4:11,12-tetracarboxdiimide (DUO-TDI) decorated with long branched alkyl chains on both imide nitrogen atoms was designed and synthesized. The supramolecular assembly behaviors of DUO-TDI in solution and at the liquid-solid interface were both investigated. The assembled nanostructures and photophysical properties of TDI in solution were explored by varying solvent polarity with spectral methods (UV-Vis, FL and FT-IR) and morphological characterization (AFM). Depending on the solution polarities, fibers, disk structures and wires could be observed and they showed diverse photophysical properties. In addition, the interfacial assembly of DUO-TDI was further investigated at the liquid-Highly Oriented Pyrolytic Graphite (HOPG) interface probed by scanning tunneling microscope (STM). Long range ordered monolayers composed of lamellar structures were obtained. The assembly mechanisms were studied for DUO-TDI both in solution and at the interface. Our investigation provides alternative strategy for designing and manipulation of supramolecular nanostructures and corresponding properties of TDI based materials.